2014
DOI: 10.1080/03033910.2015.1011193
|View full text |Cite
|
Sign up to set email alerts
|

An examination of gender differences in the impact of individual and organisational factors on work hours, work-life conflict and psychological strain in academics

Abstract: The current study used multi-group structural equation modeling (SEM) to test a fully-and partially-mediated Extended Rational Model of Work-Life Conflict and examined the impact of job involvement, workaholism, work intensity, organisational expectations and support, and having children on work hours, worklife conflict and psychological strain in male and female academics. In total, 410 academics from three Irish universities completed an electronic questionnaire survey.Results indicated both commonalities an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 43 publications
(50 reference statements)
1
34
0
1
Order By: Relevance
“…Evidence was found that over-commitment is an independent risk factor for wellbeing in academic working environments, as excessive involvement in the job role and a reluctance to disengage from it can threaten mental health and may compound the negative effects of high effort/low reward conditions. This supports previous research that has found high levels of job involvement in academic employees (Hogan et al, 2014) and highlights the negative implications the implications for work-life balance and recovery.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Evidence was found that over-commitment is an independent risk factor for wellbeing in academic working environments, as excessive involvement in the job role and a reluctance to disengage from it can threaten mental health and may compound the negative effects of high effort/low reward conditions. This supports previous research that has found high levels of job involvement in academic employees (Hogan et al, 2014) and highlights the negative implications the implications for work-life balance and recovery.…”
Section: Discussionsupporting
confidence: 78%
“…Several studies have found a high level of job involvement among academics, who typically work within a culture where long working hours and a poor worklife balance are normalised, or even celebrated (e.g. Hogan, Hogan, Hodgins, Kinman, & Bunting, 2014;Kinman & Jones, 2008). Although 'loving one's job' can benefit health and be critical for career success (Kelloway, Inness, Barling, Francis, & Turner, 2010), employees who are over-committed to work are at particular risk of work-related stress due to limited recovery opportunities (Avanzi, van Dick, Fraccaroli, & Sarchielli, 2012;Siegrist et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Tytherleigh et al (2007) found that men were more distressed than women by stressors associated with salary and benefits. Hogan et al (2014) found that women reported that they were faced with higher organisational expectations to work long hours, that women's work intensity tended to be higher than men's, and that women exhibited lower work enjoyment and job involvement than men. There were conflicting findings regarding the amount of organisational support women received, with some reporting more organisational support for women (Hogan et al 2014) and others reporting that women perceived their organisational work environments as non-supportive with regard to career development (Michailidis, 2008).…”
Section: Gendermentioning
confidence: 97%
“…Hogan et al (2014) found that women reported that they were faced with higher organisational expectations to work long hours, that women's work intensity tended to be higher than men's, and that women exhibited lower work enjoyment and job involvement than men. There were conflicting findings regarding the amount of organisational support women received, with some reporting more organisational support for women (Hogan et al 2014) and others reporting that women perceived their organisational work environments as non-supportive with regard to career development (Michailidis, 2008). Issues related to sexism in the workplace were mentioned by one study in the sample, bringing light to issues such as individualised competition and performance metrics, with women reporting a lack of recognition, respect and equal opportunity, as well as the devaluation of their work (Mountz, 2016).…”
Section: Gendermentioning
confidence: 97%
See 1 more Smart Citation